2021
DOI: 10.31635/ccschem.020.202000285
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Ion-Specific Behaviors and Design Strategies for Ion–π Interactions

Abstract: Ion-π interactions play a critical role in many important biological processes, such as gene expression, nicotine addiction, ion channel function, and so on, through recognizing specific ions by the receptors. However, widely used models, such as electrostatic potential and quadrupole moment, either treat ions as point charges or consider arenes only such that the key role of the information carried by ions is rarely discussed. Here, we shed light on the ion specificities in ion-π interactions by correlating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…It was suggested that cation−π interactions are essentially electrostatic attractions. , To date, the electrostatic model is still one of the popular tools to predict the binding ability of new cation−π systems. Considering the complex physics and multiple influencing factors of cation−π interactions, various methods, such as density functional theory, second-order Møller–Plesset perturbation theory, and Hartree–Fock theory, have also been applied to investigate cation−π interaction energies. According to computer simulations, the binding energies of model systems for different cations follow the trend of Mg 2+ > Ca 2+ > Li + > Na + > K + ≈ NH 4 + > NMe 4 + in the gas phase . Moreover, the theoretical strength of cation−π interactions is two times larger than that of salt bridges in aqueous media, highlighting their importance for protein engineering …”
Section: Characterization and Modulating Parameters Of Cation−π Inter...mentioning
confidence: 99%
“…It was suggested that cation−π interactions are essentially electrostatic attractions. , To date, the electrostatic model is still one of the popular tools to predict the binding ability of new cation−π systems. Considering the complex physics and multiple influencing factors of cation−π interactions, various methods, such as density functional theory, second-order Møller–Plesset perturbation theory, and Hartree–Fock theory, have also been applied to investigate cation−π interaction energies. According to computer simulations, the binding energies of model systems for different cations follow the trend of Mg 2+ > Ca 2+ > Li + > Na + > K + ≈ NH 4 + > NMe 4 + in the gas phase . Moreover, the theoretical strength of cation−π interactions is two times larger than that of salt bridges in aqueous media, highlighting their importance for protein engineering …”
Section: Characterization and Modulating Parameters Of Cation−π Inter...mentioning
confidence: 99%
“…Here we aim to provide a wide-scope molecular tool to quantify and picture the different binding behavior in anion- interacting systems. The current design is based on the use of benzene triimide (BTI) 34 and the theoretical guidance for ion- interactions, 39 following three considerations: 1) BTI bearing a high quadruple moment (Q ZZ = 14.5 B) enables enhanced anion- interactions; 2) the extending surface of BTI provides multiple binding sites (both the six-and five-membered rings are available to accept an anion), which should be advantageous for accommodation of differently-shaped and polydentate anions; 3) appropriate separation between the two BTI planes is crucial: A small distance is good for achieving high specificity toward given anions like N 3as previously demonstrated with the small cage 1, 34 while a too large distance would weaken the additivity or cooperativity. Thus, a triangular prism cage 2 with BTI as the bases, 2,7naphthalene dimethyl as the spacers is designed (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the cationic CPs with quaternary ammonium groups could attach and insert the bacterial membrane via electrostatic and hydrophobic interactions. It has been reported that the hydrophobic interaction is hard to affect the zeta potential of bacteria, yet the electrostatic interaction would cause a positive potential shift ( 38 ). The remarkable potential change of the PMNT/ S. oneidensis group was attributed to the electrostatic interaction.…”
Section: Resultsmentioning
confidence: 99%